Effects of a Mixture of Wood Charcoal Powder and Wood Vinegar Solution on Escherichia coli, Ammonia Nitrogen, Vitamin C and Productive Performance of Laying Hens - Sittiya , Janjira; Yamauchi, Koh-en; Yamauchi, Kohsyo; Phuchivatanapong, Phunnathorn (International Journal of Poultry Science, 2018)
Background and Objective: This study was conducted to investigate the effects of a mixture of wood charcoal powder and wood vinegar solution (WCV) on Escherichia coli (E. coli), ammonia nitrogen and vitamin C on the production performance of laying hens. Methodology: At 64 weeks of age, 96 laying hens were divided into four groups on an equal-weight basis. Each group of 24 birds had four replicates. The basal mash diet (2,600 kcal kg–1 metabolizable energy and 170 g kg–1 crude protein) was formulated to meet the nutritional requirements for layers. The basal diet was supplemented with wood charcoal powder and wood vinegar solution (WCV) at 0 (control group), 1, 2 or 3%. Results: At 72 weeks of age, all parameters of productive performance showed the highest values in the 2% dietary WCV group. The yolk color and Haugh unit, however, were the highest in the 3% dietary WCV group (p<0.05). The fecal E. coli concentration increased at the early stage of 66 weeks of age in the 1% dietary WCV group, with no change in ammonia nitrogen. Conclusion: These results may be attributed to the reducing power of WCV itself and to the vitamin C increase through WCV. These factors, by amplifying the anaerobic environment of the intestinal lumen, increased E. coli concentrations and thereby improved production performance by effectively using ammonia nitrogen. This outcome was due to the 2-3% WCV supplementation, which is most suitable for tropical climates.